E-module of mangrove ecosystem (emme): development, validation and effectiveness in improving students’ self-regulated - Irma Aprilia; I Gusti Putu Suryadarma (Biosfer: Jurnal Pendidikan Biologi, 2020)
One of the mangrove forests in Indramayu, West Java, Indonesia that plays an essential role in the environment and becomes a learning center, is the Karangsong mangrove forest. The study aimed to determine the feasibility and effectiveness of Enrichment E-Module of Mangrove Ecosystem (EMME) to improve students' self-regulated learning. This study was Research & Development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This study was conducted at a Senior High School in Sindang, Indramayu, Indonesia with ten (X) grade of science class. The samples were chosen using a purposive sampling technique, resulting in class X-7 chosen as a control group and class X-8 as an experimental group. The design of this study used a non-equivalent control group design. The average validation result by experts was that media expert of 87.75 (very feasible), material expert of 94.36 (very feasible), and biology teacher of 93.40 (very feasible). The results indicated that the enriched e-module of the mangrove ecosystem was feasible in enrichment learning. E-module did not significantly influence to improve students' self-regulated learning, as seen from the result of the Mann Whitney test (0.077). Improvement of students' self-regulated learning was low, as seen from the N-gain score of the control group (0.06) and the experimental group (0.20). These concluded that the e-module of the mangrove ecosystem could be used in the learning, and short time allocation causes the module not to influence self-regulated learning significantly. Several revisions are needed in order to make the e-module more effective in improving students' self-regulated learning.